Philippine politics and governance - Pawilen, R. A.; Pawilen, Reidan M. (Quezon City. Rex Book Store, Inc., 2017)
"This textbook provides the basic concepts and ideas regarding politics and governance in the Philippine context. In compliance with the Department of Education's K to 12 Curriculum, this book further encourages the students to explore their historical perspective and sociocultural setting to help them understand and contextualize the lessons through research-oriented activities that utilize and develop various 21st century skills. Following the principle "less is more,'' this book also offers concise discussions on the essentials of the Philippine politics and governance. These discussions are detailed, to make the subject and enable them to analyze the political processes involved in their daily lives, yet simple enough for an easy and enjoyable learning experience".
Includes glossary and references.
English text.
Keywords: Philippine-- politics and governance